Collaborative professional identities and continuity of practice: a narrative inquiry of preschool and primary teachers. Issue 3 (26th May 2020) - Sisson, Jamie Huff; Giovacco-Johnson, Tricia; Harris, Pauline; Stribling, Jodie; Webb-Williams, Jane
Abstract: This paper focuses on collaboration between Australian preschool and primary school teachers co-located on same sites, with a view to understanding and strengthening collaboration for supporting continuity of practice across preschool and primary school settings. Based on findings from a narrative inquiry study framed by Freire's notion of dialogic encounters, we examine teachers' challenges to collaboration within an Australian public education system, understood through their perspectives and enactment of their professional identities as collaborators in this physically shared space. We present a possible framework for creating a shared space in which preschool and primary teachers collaborate to support continuity of learning for children.